Application of modified sodium alginate hydrogel for interventional embolization of hemorrhagic diseases - Wei, Shengchao; Deng, Tang; Wu, Caixia; Shi, Jianshan; Liao, Yong; Huang, Lin; Liu, Yongjie; Zhong, Shijie; Ji, Xueying; Jin, Guiyun (Frontiers in Materials, 2024)
Traditional particulate embolic agents are small in diameter, but can easily embolize the ends of blood vessels, resulting in ischemia and necrosis of normal tissues and organs. The metal spring embolic agent has a larger diameter, but it cannot be degraded and can easily cause permanent damage to blood vessels. Ideally, a bleeding embolism should achieve rapid hemostasis without causing long-term necrosis of organs and tissues. In this study, a modified sodium alginate hydrogel (MSAH) was prepared by mixing an oxidized sodium alginate (OSA) aqueous solution with a carboxymethyl chitosan (CMC) aqueous solution at a ratio of 1:6 in a 38℃ bath for 8 minutes. The feasibility of this modified hydrogel was then tested in an internal iliac artery hemorrhage model using New Zealand rabbits. The MSAH had good adhesion. The hydrogel was injected through a single curved 4F catheter without obvious effects on uterine smooth muscle cell proliferation and apoptosis. The blood flow of the internal iliac artery was restored by long-term degradation of the sodium alginate hydrogel, and no ischemia and necrosis were observed by histopathology. The MSAH prepared using a mixture of OSA and CMC had good adhesion, biocompatibility, and injectability and could be used for targetvessel embolization in an internal iliac artery hemorrhage model. The MSAH can achieve main artery embolization without affecting the peripheral artery blood supply, resulting in both shortterm rapid hemostasis and long-term degradation, with no target organ necrosis.